To Study Gen-Z Preference Over Detergent VS Liquid for Cleaning Clothes in Washing Machine in Ahmedabad City - Gelani, Daya; Vaniya, Pranay; Vidani, Jignesh (MultiTech Publisher, 2024)
This study investigates the detergent preferences of Gen-Z consumers in Ahmedabad, focusing on their choice between powder and liquid detergents for laundry cleaning. By examining factors such as product switching motivations, satisfaction with detergent types, and perceived product efficiency, the research aims to uncover the key determinants influencing Gen-Z’s detergent choices. Using a quantitative approach, the study employs Chi-square tests to analyse the association between age and various factors, such as reasons for switching products, frequency of purchase, satisfaction levels, and ease of use. The results reveal that age does not significantly impact preferences for powder or liquid detergents, suggesting that Gen-Z's purchasing decisions are influenced by factors beyond age, including sustainability, convenience, and pricing. While no significant relationships were found between age and detergent-related behaviours, the findings highlight the importance of eco-friendly packaging, product innovation, and digital marketing in appealing to this consumer segment. The study suggests that Gen-Z values environmentally responsible products, ease of use, and affordability, which may drive their choices over traditional factors like brand loyalty. The practical implications for detergent brands include adopting sustainable practices, leveraging social media for marketing, and offering personalized, convenient product solutions. This research provides valuable insights for businesses aiming to capture the attention of Gen-Z consumers in the detergent market and beyond